A Semiotic Analysis of Social Criticism in Robert Zemeckis’s Forrest Gump Movie (1994) - Rutsyamsun, Vidi; Sakinah, R. Myrna Nur (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
This article examines the semiotic analysis of social criticism in Robert Zemeckis’s Forrest Gump Movie (1994) using Ferdinand De Saussure's semiotic theory. According to Saussure's theory, the sign consists of two interconnected elements: the signifier and the signified. Thus, the purpose of this study is to highlight the social criticism signs present in the Forrest Gump story and to highlight how crucial it is for literary works to reflect a real society through social criticism. The Forrest Gump film was chosen as the object of research because researchers are interested in exploring social criticism messages that are represented in the movie. In this context, the researchers believed that Forrest Gump movie which tell story about a man (Forrest) who has intelligence problems and becomes the object of ridicule in the social sphere and his life provided meaningful messages through the screenplay of the movie.